WRITING JOB APPLICATION LETTER AND RESUME WITH GOOGLE DOCUMENT: AN EXPERIMENTAL RESEARCH - Marisa Fran Lina (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
One of the main skills that must be mastered by vocational students, especially in the Department of Office Automation & Governance (OTKP) is understanding the script layout in English correspondence activities. Considering the urgency of the letter that will be used frequently in the future, and based on discussions with the class teacher at the research locus, the researcher focused on studying the writing of job application letters and resumes in English written by the vocational students. In addition, with the development of writing technology by Google Document (Google Docs/GDocs), it is hoped that it can facilitate students' writing assignments. This research is an experimental study that examines the effectiveness of Google Docs in writing job application letters and resumes in English. The research was conducted through pre-test, post-test and Forum Group Discussion (FGD) in order to provide input on research results. The results shows that through the t test, it is found that Google Docs is effective in writing English correspondence compared to writing letters manually in class X OTKP of  SMK Negeri 1 Salatiga.